A survey on knowledge, attitude & confidence level of disaster management among doctors in Terengganu. - Mustafa, Muhamad Sukri (2015)
Background Disasters are unpredictable events that kill and affect people, demolish properties and disrupt environment. During such events, doctors play a vital role in dealing with the victims. It is crucial for doctors especially doctors working in emergency department to be prepared in facing the aftermath of disasters. The aim of this study was to evaluate the level of knowledge, attitude and confidence level of disaster management among doctors working in emergency department. Methodology This is a cross-sectional study using convenient sample conducted in all emergency department in Terengganu. A questionnaire was designed based on National Security Council under Directive No. 20, hospital disaster plan and review of relevant literature. It was edited by two emergency physicians and pre-test was conducted in HUSM to validate and test the reliability of the questionnaire. All doctors working in emergency department in Terengganu were included in this study. The study was conducted from January 2014 till March 2014. The questionnaires were circulated with help from representative from each hospital. It was anonymous and no time limit. The questionnaires were then collected and coded accordingly. Statistical analysis was used using SPSS version 21. Result A total of 92 doctors were analyzed. Average age was 28 years and 62% of doctors were from emergency department with in-house emergency physician. 28% of respondent had attended disaster drill previously and only 13% of doctors who had experienced in dealing with real disaster. The mean knowledge, attitude and confidence level were 72.14, 75.20, and 16 percent, respectively. Previously attended disaster drill was found to significant factors for good knowledge (p=0.000) and increase confidence level (p=0.03). Service duration and duration of working in emergency department were also found to be significant factors affecting knowledge (p=0.008) and attitude (p=0.000) towards disaster management. Conclusion We concluded that the knowledge regarding disaster management among doctors in Terengganu was at an average level. However, the majority of emergency doctors were found to have positive attitude towards disaster management. Despite this, self reported confidence was poor among doctors working in emergency department. Our results also suggest that advanced life support (e.g. TLS, ATLS) and frequent involvement in disaster drills are important for effective management of disaster in the future.